1997
DOI: 10.1021/ma970024z
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Syndiotactic Polystyrene in β-Form. 1. Positional Identification of Stacking Faults in the Solution-Grown Single Crystals

Abstract: The locations of the stacking faults in -form single crystals of syndiotactic polystyrene, which were grown isothermally from a dilute solution at temperatures ranging from 150 to 210°C, were identified in high-resolution and dark-field (DF) images taken by transmission electron microscopy. The shift or kink of the (210) lattice fringes, which shows the position of the fault, was directly detected in the high-resolution images. DF images taken using several reflections exhibited irregularly spaced striations p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 11 publications
1
56
1
Order By: Relevance
“…: +886 3 5712121x55306; fax: +886 3 5724727. the initial zig-zag planar structure of the chain into helical structure without destroying the orientation of fibers. The same solvent was also utilized to produce the crystallization in glassy sPS [5][6][7]. Greis et al [8] completed the structure characterization, reporting that three sPS macromolecules from clusters have two types of handedness.…”
Section: Introductionmentioning
confidence: 99%
“…: +886 3 5712121x55306; fax: +886 3 5724727. the initial zig-zag planar structure of the chain into helical structure without destroying the orientation of fibers. The same solvent was also utilized to produce the crystallization in glassy sPS [5][6][7]. Greis et al [8] completed the structure characterization, reporting that three sPS macromolecules from clusters have two types of handedness.…”
Section: Introductionmentioning
confidence: 99%
“…The irregular folding habit of the sPS chains is further supported by a recent finding that the fold surface energy of the b 0 -form sPS lamellae is only slightly larger than its lateral surface energy [37]. The lack of uniform folding directions plausibly resulted from the presence of stacking faults [41,43], which influence the new polymer stem to attach onto the growth face. Essentially, the polymer chains on the lamellar surface are not tightly folded but act like ''floating segments'' [42] which possess sufficient mobility for conformation change induced by appropriate thermal treatments.…”
Section: A Proposed Mechanism For Re-crystallizationmentioning
confidence: 63%
“…Then another crucial question arises: where do the thickened lamellae associate with the re-crystallization process? Using a decoration method [40], Tosaka et al [41] and Ho et al [42] have shown that the polymer chains are irregularly folded even in the single lamellar crystals of sPS. The irregular folding habit of the sPS chains is further supported by a recent finding that the fold surface energy of the b 0 -form sPS lamellae is only slightly larger than its lateral surface energy [37].…”
Section: A Proposed Mechanism For Re-crystallizationmentioning
confidence: 99%
“…54,55 Disorder in the stacking of ordered ac layers of chains along one direction is present, according to X-ray 54 and electron diffraction patterns. 188 The structure has been described in terms of two limit models; a limit-ordered β -form, described by the space group P 2 1 Figure 2.43. A regular succession of bilayers ABAB.…”
Section: Disorder In Stacking Of Ordered Layers Of Macromolecules Alomentioning
confidence: 99%